1999
DOI: 10.1007/s11745-999-0458-5
|View full text |Cite
|
Sign up to set email alerts
|

Infant cerebellar gray and white matter fatty acids in relation to age and diet

Abstract: There is little evidence as to the fatty acid composition of the cerebellum in infancy and it remains uncertain whether milk diet can influence its composition. We therefore examined cerebellar gray and white matter of infants less than 6 month old who had died unexpectedly. The fatty acid content of 33 gray and 21 white matter specimens from infants born at term and 6 gray and 5 white matter specimens from preterm infants was assessed by gas chromatographic/mass spectrometric analysis. Infants were grouped ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…1, panels A and C) proved different from the relation with AA. Generally, brain DHA is more sensitive to dietary DHA than brain AA is to dietary AA, which has been shown in baboons [35] and may also be derived from autopsy studies in breast and formula fed infants [36][37][38]. The descending part of the U-shaped relation between GM quality and the iRBC DHA/AA ratio (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…1, panels A and C) proved different from the relation with AA. Generally, brain DHA is more sensitive to dietary DHA than brain AA is to dietary AA, which has been shown in baboons [35] and may also be derived from autopsy studies in breast and formula fed infants [36][37][38]. The descending part of the U-shaped relation between GM quality and the iRBC DHA/AA ratio (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…However, animal studies have shown that when n-3 fat sources are inadequate during early neural development, then the levels of brain and retinal DHA decline (4,(20)(21)(22)(23)(24). This has also been confirmed in autopsy studies of human infants that were fed a vegetable oil-based formula with low n-3 fat sources vs. breast-feeding in which preformed DHA was present (25)(26)(27). This has naturally led to an interrogation of the functional consequences of neural DHA loss.…”
Section: Dha Compositionmentioning
confidence: 88%
“…As mentioned above, formula-feeding of infants has been associated with a loss in brain DHA with respect to the level in those breast-fed (25)(26)(27). The pre-existing animal literature would predict that formula-fed infants would have a functional deficit if the neural DHA loss were of a sufficient magnitude.…”
Section: Human Studiesmentioning
confidence: 97%
“…AA and DHA as a proportion of total fatty acids are shown for the diet of pregnant mothers (Lakin et al, 1998), 1 the adipose tissue (Leaf et al, 1995), 2 maternal and cord blood plasma phospholipids (Otto et al, 1997), 3 triglyceride (Berghaus et al, 2000), 4 cholesterol ester (Hoving et al, 1994), 5 and NEFA (Benassayag et al, 1999), 6 the placental microvillous and basal membranes (Powell et al, 1999), 7 and adipose tissue and brain at birth (Clandinin et al, 1981 Figure 3 The theoretical rate of oxidation was calculated from the rate of maternal energy expenditure (9453 MJ/day), the proportion of that energy derived from fat (30%), the energy content of fat (39 kJ/g) (Butte, 2000) and the proportion of DHA in the oxidised fat (0.1% DHA; Figure 2). The DHA content of fetal tissues was calculated from the lean mass (calculated as body weight minus the weight of fat, skeleton and skin (Widdowson, 1974)), the fat mass (Widdowson, 1974) and the weight of the placenta (Hytten, 1974) and brain (Clandinin et al, 1980) and the fat and DHA concentration of the brain (Clandinin et al, 1980;Jamieson et al, 1999), placenta (Widdowson & Spray, 1951;Lakin et al, 1998) and adipose tissue (Clandinin et al, 1981). For the purposes of the calculation the DHA content of the fetal lean tissue, blood vessels, etc, was assumed to be the same as the placenta.…”
Section: Importance Of Fatty Acids To the Fetusmentioning
confidence: 99%
“…It has also been deduced from these tracer studies that the rate of AA synthesis is significantly greater than that for DHA. Additional circumstantial evidence that the human infant is better able to synthesise AA than DHA comes from the observation that the concentration of DHA in the neonatal brain is dependent on the intake of preformed DHA, while there is little effect of AA intake on the brain concentration (Farquharson et al, 1993;Makrides et al, 1994;Jamieson et al, 1999). This difference in synthesis is consistent with the biochemical pathways involved as the final step in the synthesis of DHA is considerably more complex than that for AA (Figure 1) in that it requires the participation of enzymes in both peroxisomes and the endoplasmic reticulum as well as the controlled movement of fatty acids between these two cellular compartments (Sprecher & Chen, 1999).…”
Section: Synthesis Of Lcpufamentioning
confidence: 99%